Case Report: Innovative surgical management of ileal neobladder fistula after radical cystectomy - Ma, Zhiyang; Ji, Xiaopin; Rui, Wenbin; Wang, Xiaojing (Frontiers in Oncology, 2025)
An ileal neobladder fistula is a rare but serious complication of radical cystectomy with orthotopic neobladder reconstruction. Owing to its low incidence, the challenges posed by dense adhesions, and the risk to urinary function, there is little consensus on optimal management. A 68-year-old male with low-grade non-muscle-invasive bladder cancer underwent transurethral resection, followed by radical cystectomy and total laparoscopic orthotopic neobladder reconstruction. One month after surgery, the patient developed fecaluria. Imaging revealed a fistula between the neobladder and the ileum. Proximal ileostomy was performed to eliminate fecaluria. Seven months later, an open surgical repair was performed. Severe adhesions around the original ileal anastomosis and neobladder apex precluded safe separation. Rather than risking neobladder injury and loss of capacity, the surgical team preserved approximately 2 cm of the adherent ileum and restored intestinal continuity using overlap anastomosis. Postoperative recovery was uneventful, and follow-up revealed no recurrence of the fistula. This case demonstrates that the rapid identification and staged management of ileal neobladder fistulas can ensure favorable outcomes. The innovative surgical approach described here is effective in preserving both neobladder function and intestinal integrity and provides a viable, less invasive alternative for patients presenting with complex adhesions.